Signal Strength Based Sybil Attack Detection in Wireless Ad Hoc Networks - Abbas, S.; Merabti, M.; Llewellyn-Jones, D. (2009 Second International Conference on Developments in eSystems Engineering, 2009)
Signal Strength based position verification is more promising as compared to other Sybil attack detection techniques because it is lightweight and does not require centralisation. Nodes can locally determine their locations through received signal strength variations and inform neighbours about location updates accordingly. In position verification, network nodes verify the position of each node and further ensure that each physical location is bounded by only one identity at any particular time. In this paper we will survey Sybil attack detection techniques and their related issues. Finally we will present our ideas about the Sybil attack detection via one-time localization (only at the entrance into the network) which significantly reduces the communication overhead unlike other schemes where per packet location tracking or periodic dissemination of location information is used to detect Sybil attacks.